Do Internal Control Weaknesses Affect Firms’ Demand for Accounting Skills? Evidence from U.S. Job Postings - Gao, Janet; Merkley, Kenneth J.; Pacelli, Joseph; Schroeder, Joseph H. (The Accounting Review, 2023)
ABSTRACT In this study, we examine whether firms respond to internal control weaknesses (ICWs) by requiring accounting-specific skills when hiring rank-and-file employees. Using unique data containing an extensive collection of job postings, we document significant increases in firms’ job postings that list accounting skills after the disclosure of an ICW. This effect is more pronounced for firms with better financial resources and when ICWs are more severe or personnel-related. In addition, our results extend to employees that are not specifically designated as accountants, suggesting a broader role for rank-and-file employees in influencing internal control quality. Finally, we find that increases in job postings with accounting skill requirements are associated with improvements in internal controls and a higher likelihood of ICW remediation. Overall, our findings shed new light on how firms respond to ineffective internal controls by increasing their emphasis on accounting skills in their workforce. Data Availability: Data are publicly available from the sources identified in the text. JEL Classifications: G30; J23; M41; M42.